Kerajaan Allah sebagai Marturia : Relevansi Ajaran Paulus bagi Masyarakat Batak - Frischa Nofrianti; Helma Siregar; Johanes Panjaitan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the relevance of Paul's teachings on the Kingdom of God in the context of marturia (testimony) for the Batak community. In Paul's teachings, the Kingdom of God is not only understood as an eschatological dimension, but also as a calling for every person to live as a Witness of Christ in the midst of the world. This teaching invites Christians to live in love, justice, and hope based on the values ​​of the Kingdom of God. For the Batak community, which has a strong social and cultural tradition, Paul's teachings on the Kingdom of God have great potential to be applied in their daily lives. This study reveals how the teachings on the Kingdom of God can have a positive impact on the formation of authentic marturia in the midst of Batak socio-cultural life. By combining the principles of Paul's teachings and Batak cultural values, this study shows that the teachings are not only relevant for spiritual life, but also for the development of a more just and prosperous society, in accordance with the principles of the Kingdom of God.